Business travel decisions and high-speed trains: an ordered logit approach - Rossi, Federica; Maggi, Rico (REGION, 2019)
The paper studies the potential impact on business travel of the new high-speed railway line project, called AlpTransit, which will link Lugano, the small economic hub of the southern part of Switzerland, with Zurich, one of the major Swiss economic centres, situated north of the Alps. Thanks to this infrastructure, travel time between the two cities will decrease considerably from about three hours to less than two hours by the end of 2020. The question that we pose in this paper is what impact high-speed trains could have, in the short to medium term, on business travel between the two hubs (ex-ante evaluation). Indeed, given the travel time, firms could increase their business-to-business one-day trips, boosting face-to-face interactions within and among enterprises. Our curiosity more specifically regards the potential impact of the change in travel time on the propensity to travel of employees with different functions in various types of firms. An on-line survey was conducted among firms located in Ticino, the Swiss Canton that includes Lugano. The data are analysed using four ordered logit models, one for each employee category (CEO, administrative staff, sales personnel, specialists), since hierarchical position and professional status influence business travel characteristics. Results show that internal firm characteristics, such as sector, frequency and destination of current business travels significantly influence the propensity to travel to Zurich more often thanks to AlpTransit.